2016
DOI: 10.1200/jco.2016.34.2_suppl.197
|View full text |Cite
|
Sign up to set email alerts
|

Radium-223 (Ra-223) re-treatment (Re-tx): First experience from an international, multicenter, prospective study in patients (Pts) with castration-resistant prostate cancer and bone metastases (mCRPC).

Abstract: 197 Background: Ra-223 tx for up to 6 injections (inj) is indicated for pts with symptomatic bone metastases. Ra-223 tx beyond 6 inj has not been previously reported. Herein we report the first safety and efficacy findings of Ra-223 re-tx from an international prospective trial in mCRPC pts. Methods: Pts with CRPC with ≥ 2 bone mets who completed 6 initial Ra-223 inj with no disease progression in bone and progressed after initial tx were potentially eligible for Ra-223 re-tx, provided that hematologic (heme)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Since its introduction, 223Radium treatment is gaining widespread use in clinical practice. During recent years, many clinical trials conducted in expanded access setting confirmed the safety and efficacy of this treatment Sartor et al, 2016;Vogelzang et al, 2015).…”
Section: Ta B L E 1 Baseline Patients' Characteristics (Ecog = Easternmentioning
confidence: 94%
See 1 more Smart Citation
“…Since its introduction, 223Radium treatment is gaining widespread use in clinical practice. During recent years, many clinical trials conducted in expanded access setting confirmed the safety and efficacy of this treatment Sartor et al, 2016;Vogelzang et al, 2015).…”
Section: Ta B L E 1 Baseline Patients' Characteristics (Ecog = Easternmentioning
confidence: 94%
“…During recent years, many clinical trials conducted in expanded access setting confirmed the safety and efficacy of this treatment Sartor et al, 2016;Vogelzang et al, 2015). During recent years, many clinical trials conducted in expanded access setting confirmed the safety and efficacy of this treatment Sartor et al, 2016;Vogelzang et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…По нашему мнению, потенциальным кан-дидатом на радий-223 может быть пациент с симптомати-ческим метастазом в кости, ограниченной тяжестью забо-левания и длительным периодом удвоения ПСА (напри-мер, 6 месяцев) или сопутствующими заболеваниями, при которых противопоказано использование химиотерапии, либо при отказе от химиотерапии. Следует отметить, что использование радия-223 не ухудшало комплаентность пациента в отношении последующей терапии доцетаксе-лом, которую можно безопасно сочетать с использовани-ем радия-223 [25].…”
Section: радий-223 способен индуцировать снижение не только костной щunclassified
“…Furthermore, in a recent international study investigating retreatment with Ra-223, investigators found that retreatment was well tolerated with minimal morbidity while mitigating bone disease progression. [ 21 ]…”
Section: Toxicitymentioning
confidence: 99%